2011
DOI: 10.1007/s10546-011-9616-2
|View full text |Cite
|
Sign up to set email alerts
|

The Near-Calm Stable Boundary Layer

Abstract: For the near-calm stable boundary layer, nominally 2-m mean wind speed <0.5 m s −1 , the time-average turbulent flux is dominated by infrequent mixing events. These events are related to accelerations associated with wave-like motions and other more complex small-scale motions. In this regime, the relationship between the fluxes and the weak mean flow breaks down. Such near-calm conditions are common at some sites. For very weak winds and strong stratification, the characteristics of the fluctuating quantities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 50 publications
1
70
0
Order By: Relevance
“…These studies reveal the uncertain relationship between fluxes and gradients in conditions of weak wind and strong stratification. Mahrt (2011) found that the turbulence within the near-calm regime (nominally winds less than 0.5 m s −1 ) is not closely related to the weak mean wind, but is instead related to short-term accelerations associated with submesoscale motions. The current study extends this analysis to different features of the turbulence and employs a much larger dataset that includes more extremely stable conditions as well as a significant number of nearneutral near-calm conditions.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…These studies reveal the uncertain relationship between fluxes and gradients in conditions of weak wind and strong stratification. Mahrt (2011) found that the turbulence within the near-calm regime (nominally winds less than 0.5 m s −1 ) is not closely related to the weak mean wind, but is instead related to short-term accelerations associated with submesoscale motions. The current study extends this analysis to different features of the turbulence and employs a much larger dataset that includes more extremely stable conditions as well as a significant number of nearneutral near-calm conditions.…”
Section: Introductionmentioning
confidence: 95%
“…Generation of turbulence in very weak-wind stable conditions is poorly understood and does not satisfy existing similarity theory (Grachev et al, 2005;Basu et al, 2006;Mahrt and Vickers, 2006;Sorbjan, 2010;Mahrt, 2011). These conditions generally correspond to very small averaged turbulent heat flux, as in the radiative regime of Van de Wiel et al (2003).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The gray vertical lines indicate events with U < 0.5 m s −1 , the threshold for the near-calm stable boundary layer (SBL), when, according to [98], the relationship between the fluxes and the weak mean flow breaks down and the use of the traditional stability parameters, e.g., ζ, Ri B , R f , becomes difficult. The dynamic stability, ζ, covers a wide range of different stabilities from weakly unstable (4%), ζ < −0.1, to stable or very stable (29%), ζ ≥ 0.05, with most observations in the near-neutral range (66%), −0.1 ≤ ζ < 0.05.…”
Section: Surface Layer Observationsmentioning
confidence: 99%